2015
DOI: 10.1021/acssuschemeng.5b00627
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Synthesis of SnWO4 Nanoassemblies on DNA Scaffold: A Novel Material for High Performance Supercapacitor and as Catalyst for Butanol Oxidation

Abstract: Self-assembled, aggregated SnWO 4 nano-assemblies are formed by the reaction ofSn(II) salt and Na 2 WO 4 .2H 2 O in the presence of DNA under microwave heating within six minutes. We have emphasized the natural properties of DNA with its ability to scaffold SnWO 4 nano-assemblies and examined the role of starting reagents on the particles morphology. The diameter of the individual particles is ultra-small and varies from ~ 1-2.5 nm. The potentiality of the SnWO 4 nano-assemblies has been tested for the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 70 publications
3
53
0
Order By: Relevance
“…Sivasankara Rao Ede and Subrata Kundu observed similar type of XRD pattern for β-SnWO4 nanomaterials. So from the XRD analysis we confirmed that the synthesized SnWO4 NPs are pure and crystalline in nature [16]. The cubic structure of β-SnWO 4 belonging to (P2 1 3 or T 4 ) space group [27].…”
Section: Electrode Fabrication For Lithium Ion Batterymentioning
confidence: 52%
See 1 more Smart Citation
“…Sivasankara Rao Ede and Subrata Kundu observed similar type of XRD pattern for β-SnWO4 nanomaterials. So from the XRD analysis we confirmed that the synthesized SnWO4 NPs are pure and crystalline in nature [16]. The cubic structure of β-SnWO 4 belonging to (P2 1 3 or T 4 ) space group [27].…”
Section: Electrode Fabrication For Lithium Ion Batterymentioning
confidence: 52%
“…LIBs play an important role in the current profile due to their high gravimetric and volumetric energy, high cycle life, high power density and long self-discharge properties [15]. The most effective approaches include: (1) reducing particle size to nanoscale for alleviating mechanical strain: (2) forming the hierarchical porous structure to provide a stable solid electrophilic interphase layer of the inner pore that provides adequate space for expansion; dispersing amorphous nano-sized materials [16]. Lithiation/delithiation of Li + ions during charge/discharge correlates with a change in the oxidation state of transition metal electrodes [17].…”
Section: Introductionmentioning
confidence: 99%
“…The as‐prepared CuWO 4 electrode exhibited a specific capacitance of 77 F g −1 at 20 mV s −1 . Ede and Kundu reported the microwave‐assisted synthesis of SnWO 4 nanoassemblies on a DNA scaffold for SCs . The SnWO 4 nanoassemblies were synthesized through the anion‐exchange reaction of Sn II chloride with sodium tungstate (Na 2 WO 4 ⋅ 2 H 2 O), with the assistance of DNA under microwave heating.…”
Section: Current Advances In Wo3‐based Scsmentioning
confidence: 99%
“…[115] An anocomposite electrode was prepared on ag lassy carbon currentc ollector and then applied as aS C. The as-prepared CuWO 4 electrode exhibitedaspecific capacitance of 77 Fg À1 at 20 mV s À1 .E de and Kundu reported the microwave-assisted synthesis of SnWO 4 nanoassemblies on aD NA scaffold for SCs. [116] The SnWO 4 nanoassemblies were synthesized through the anion-exchange reaction of Sn II chloride with sodium tungstate (Na 2 WO 4 ·2H 2 O), with the assistanceo fD NA under microwave heating. The SnWO 4 nanoassemblies showed as pecific capacitance of 242 Fg À1 at 5mVs À1 and ac apacity retention of 85 %o ver 4000cycles.D ing et al reported the fabrication of Co 3 O 4 -CoWO 4 heterojunctionst hrough at wo-step hydrothermal method.…”
Section: W-based Binary Metal Oxide Composite Materialsmentioning
confidence: 99%
“…Fig. d illustrated a single spectral peak of the O 1s group demonstrating the presence of only one oxygen species in the crystal lattice. From the BE value (531.0 eV) the existence of O(2–) species could be confirmed, and the metal (Sn)‐oxygen BE difference (35.64 eV) indicated the predominance of strong electronic interactions of oxygen with the dopant (Sn) .…”
Section: Resultsmentioning
confidence: 99%